Clinical research on the use of bordered foam dressings in the treatment of complex wounds: A systematic review of reported outcomes and applied measurement instruments. Issue 3 (August 2022) - Raepsaet, Charlotte; Alves, Paulo; Cullen, Breda; Gefen, Amit; Lázaro-Martínez, José Luis; Lev-Tov, Hadar; Najafi, Bijan; Santamaria, Nick; Sharpe, Andrew; Swanson, Terry; Woo, Kevin; Beeckman, Dimitri
Abstract: Objective: The aim of this review article was to identify reported outcomes and measurement instruments used in clinical research on bordered foam dressings in the treatment of complex wounds. Methods: MEDLINE (PubMed interface), Cumulative Index to Nursing and Allied Health Literature (CINAHL), EMBASE, and The Cochrane Library were systematically searched using a combination of key terms including; wounds, bordered foam dressing, and treatment. Studies were included if they (1) targeted an adult population, (2) addressed the treatment of complex wounds with a bordered foam dressing as the primary wound dressing, (3) were retrieved from original research, and (4) were published between 2000 and 2022. There were no restrictions on language or study design. Studies that focused primarily on the prevention of complex wounds were excluded. Data extraction included outcome domains, outcomes, instruments, time points, and outcome measures. The OMERACT Filter 2.0 was used as a conceptual framework for the extraction of outcomes. Results: A total of 24 outcome domains and 82 outcomes were identified. The outcomes were categorised into five core areas: (1) impact on life, (2) dressing performance, (3) pathophysiological manifestations, (4) resource use, and (5) adverse events. Thirtynine outcomes (47.0%) were measured at more than one time point. The most frequently reported time point was 'at the end of treatment' (62.7%). Outcomes were measured using self-report instruments, clinical observations, and bio-physiological instruments. Conclusion: This systematic review identified reported outcomes and measurement instruments in research on bordered foam dressings in the treatment of complex wounds. The variety and lack of consistency in terms of instruments, time points and outcome measurements made it difficult to compare data directly across different reported studies. A solution to the variety in outcome reporting across studies in complex wound care, and moreover for the treatment with bordered foam dressings, is the development of a Core Outcome Set (COS). The outcomes in this review article will inform the next steps of developing a COS, where patients, clinicians and researchers will be involved to decide on the final outcomes included in a COS for the treatment of complex wounds with bordered foam dressings. Highlights: The incomparability in outcomes makes it difficult to evaluate clinical trials in complex wound care in a uniform way. Future research should investigate which outcomes are important to patients. The development of a COS is a solution to the variety in outcome reporting across studies in complex wound care.